Analisis Hukum Implementasi Kebijakan Terkait Pencemaran Udara Dalam Upaya Mitigasi Penyakit Infeksi - Kesuma, Aghesna Rahmatika; Wulandari, Christine; Bakri, Samsul; Sukohar, Asep; Kesuma, Arsyad Sobby (Universitas Sang Bumi Ruwa Jurai, 2024)
Environmental protection is becoming increasingly important in the face of the negative impact on human health. This article reviews the role of living environmental laws in regulating environmental pollution to prevent the spread of infectious diseases. Air pollution can cause many infectious diseases that are dangerous to the community. International regulations such as the Stockholm Convention as well as national laws such as Law No. 32 of 2009 in Indonesia, and are linked to the Omnibus Law on Job Creation No. 11 of 2020 thus providing a framework for controlling pollutants and mitigating the risk of disease infection. Case studies show how violations of the environmental laws have caused an outbreak of infectious diseases in a region. Measures such as tighter law enforcement, to maintain a safe and healthy environment, the use of environmentally friendly technologies and raising public awareness are needed. With proper implementation, habitat legislation can be an effective instrument in preventing the spread of infectious diseases through environmental pollution